Emotions, Crime Seriousness, and Alibi Believability. Issue 1 (2nd January 2018) - Snow, Mark D.; Warren, Kelly L.
Abstract : In the current study the impact of victim age, crime seriousness, and social influence on perceptions of alibi believability, victim responsibility, confidence, and emotions was examined. Participants ( N = 141) read a brief crime-scenario vignette and a summary of the suspect's alibi, followed by a series of closed-ended questions. The alibi was held constant across all conditions. Eighty percent of participants rated the suspect's alibi as moderately believable or less than moderately believable. A significant interaction of Victim Age × Crime Seriousness on perceptions of alibi believability was found. Additionally, those individuals who reported greater feelings of certain negative emotions tended to rate the crime as being more serious and the suspect's alibi as less believable. Furthermore, participants' self-reported feelings of sadness, pleasure, and fear could significantly predict participants' alibi believability ratings. These results offer additional support for the legal relevance of emotions, particularly with respect to alibi assessment.